The Social Anxiety under Corona Virus Pandemic in Millennial Generation: an Experience of Indonesia - Deri Wanto; Jalwis Jalwis (Universitas Ahmad Dahlan, 2021)
This study aimed at verifying the relationship between Covid-19 pandemic and social anxiety in the Millennial generation in Indonesia. The study used the OLS (Ordinary Least Squares) approach in analyzing the data from 441 respondents from 10 universities in Indonesia. The theory formulated as the finding of this study is: â€œThe social anxiety experienced by the Millennials during the Covid-19 outbreak is a product of social situations. It is made a convincing case because there is a correlation between the Covid-19 pandemic in terms of the perceptions and understanding of the Millennial generation in Indonesia and social anxiety. The influence of the Covid-19 pandemic on social anxiety has even significantly folded.â€Â This article is useful to show how significant the influence of Pandemic Covid-19 on Social Anxiety in Millennials in Indonesia, where such studies have not even been adequately offered by other scholars. The study not only fills the gap but precisely becomes a preliminary study that measures the correlation of Covid-19 Pandemic to social anxiety in millennial generation in Indonesia.Â Keywords: social anxiety, Covid-19 pandemic, Millennial generation, Social anxiety disorder, psychological disorder.